High resolution-ion mobility mass spectrometry as an additional powerful tool for structural characterization of mycotoxin metabolites. (15th April 2018) - Righetti, Laura; Fenclova, Marie; Dellafiora, Luca; Hajslova, Jana; Stranska-Zachariasova, Milena; Dall'Asta, Chiara
Highlights: IM-MS supports the structural identification of isomeric mycotoxin glucuronides. Good correlation between experimental and theoretical CCS was found. The inclusion of CCS values in the annotation procedure is encouraged. Abstract: This work was designed as a proof of concept, to demonstrate the successful use of the comparison between theoretical and experimental collision cross section (CCS) values to support the identification of isomeric forms. To this purpose, thirteen mycotoxins were considered and analyzed using drift time ion mobility mass spectrometry. A good linear correlation ( r 2 = 0.962) between theoretical and experimental CCS was found. The average ΔCCS was 3.2%, fully consistent with the acceptability threshold value commonly set at 5%. The agreement between theoretical and experimental CCS obtained for mycotoxin glucuronides suggested the potential of the CCS matching in supporting the annotation procedure.